2019
DOI: 10.1002/essoar.10501008.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnetic Holes Upstream of the Martian Bow Shock: MAVEN Observations

Abstract: Magnetic holes (MHs) are pressure‐balanced structures characterized by distinct decreases in the interplanetary magnetic field strength in otherwise unperturbed solar wind. In this paper we present an analysis of MHs upstream of the Martian bow shock based on 3 months of observations by the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft. Plasma properties within and around these structures as well as their shape characteristics are examined. We find an occurrence rate of around 2.1 events per day. A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…(1977) suggested that there are two types of magnetic holes: one associated with a clear rotation of the magnetic field from one side of the hole to the other (“rotational” magnetic holes), and one type without such a rotation (“linear” holes). This has been verified in several studies (Briand et al., 2010; Madanian et al., 2019; Sperveslage et al., 2000; Tsurutani et al., 2009; Volwerk et al., 2020; Winterhalter et al., 1994; Xiao et al., 2010; Zhang, Russell, Baumjohann, et al., 2008; Zhang, Russell, Zambelli, et al., 2008) at various heliocentric distances. Various definitions of linear magnetic holes have been employed, but a commonly used definition is that the angle between the magnetic field direction before and after the magnetic hole be less than 10° (Briand et al., 2010; Madanian et al., 2019; Sperveslage et al., 2000; Tsurutani et al., 2011; Volwerk et al., 2020).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…(1977) suggested that there are two types of magnetic holes: one associated with a clear rotation of the magnetic field from one side of the hole to the other (“rotational” magnetic holes), and one type without such a rotation (“linear” holes). This has been verified in several studies (Briand et al., 2010; Madanian et al., 2019; Sperveslage et al., 2000; Tsurutani et al., 2009; Volwerk et al., 2020; Winterhalter et al., 1994; Xiao et al., 2010; Zhang, Russell, Baumjohann, et al., 2008; Zhang, Russell, Zambelli, et al., 2008) at various heliocentric distances. Various definitions of linear magnetic holes have been employed, but a commonly used definition is that the angle between the magnetic field direction before and after the magnetic hole be less than 10° (Briand et al., 2010; Madanian et al., 2019; Sperveslage et al., 2000; Tsurutani et al., 2011; Volwerk et al., 2020).…”
Section: Introductionmentioning
confidence: 62%
“…This is also a typical property of magnetic mirror mode structures (e.g., Hasegawa, 1969), which has motivated several authors to suggest a connection between linear magnetic holes and the mirror mode instability, especially since mirror mode structures typically have a linear polarization (Tsurutani et al, 2011, and references therein). As support for this idea several authors (Madanian et al, 2019;Stevens & Kasper, 2007;Winterhalter et al, 1994) also cite the fact that magnetic holes are often found in regions where the solar wind plasma is either unstable or only marginally stable with respect to the mirror mode instability criterion (e.g., Southwood & Kivelson, 1993):…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The magnetic field data are from the Magnetometer sensor, which measures the magnetic field with up to 32 Hz sampling rate (Connerney et al, 2015). The ion data are from the Solar Wind Ion Analyzer (SWIA) instrument (Halekas et al, 2015), which measures ions in the 25 eV to 25 keV energy range with a 22.5° angular resolution over a total field of view of 2.8 π solid angle every 8 s. The ion moments are calculated in a similar way as in Halekas et al (2017) and Madanian et al (2019).…”
Section: Observationsmentioning
confidence: 99%
“…There were also much shorter-scale (a few second) variations throughout the cavity in the Wind data (but much less frequently in the ACE and ARTEMIS data). Many of these shorter-scale variations are the so-called magnetic holes in which magnetic field magnitude decreases down to a few nT (e.g., Turner et al 1977 ; Winterhalter et al 1994 ; Haynes et al 2015 ; Roytershteyn et al 2015 ; Volwerk et al 2020 ; Madanian et al 2020 ). Magnetic holes are typically characterized as localized (a few second duration) depressions in the magnetic field magnitude with little (< 10°) rotation.…”
Section: Observationmentioning
confidence: 99%